Efficiency of Multi Soil Layering (MSL) System in A Household Scale of Wastewater Treatment Using Environmental Friendly Materials - Badrus Zaman; Wiharyanto Oktiawan (Center for Science and Technology, IAIN Surakarta, 2020)
Most community settlements in Indonesia do not have a household scale of a wastewater treatment plant. Fatal impacts on the environment and human health can occur at any time, including (a) causing environmental damage (disaster), (b) damaging beauty/aesthetics for the scenery will be unpleasant and foul-smelling, (c) polluting water bodies, and (d ) endangering health. The purpose of this study is to optimize the Multi Soil Layering (MSL) System to treat domestic wastewater (greywater) using environmentally friendly materials that are available in Indonesia. The research method used the MSL system with the first variation using a batch system with Hydraulic retention time (HRT) for 24 hours and the second variation using an intermittent system with 3, 6, 9 hours HRT. The results showed that the MSL system was able to eliminate COD well. The highest COD removal efficiency was 93.44% at 9 hours HRT, but the effluent quality did not meet the required quality standards. The development of MSL systems that produces an effluent quality that meets the quality standards needs to be studied further.